Actinobacterial diversity in limestone deposit sites in Hundung, Manipur (India) and their antimicrobial activities - Nimaichand, Salam; Devi, Asem Mipeshwaree; Tamreihao, K.; Ningthoujam, Debananda S.; Li, Wen-Jun (Frontiers in Microbiology, 2015)
Studies on actinobacterial diversity in limestone habitats are scarce. This paper reports profiling of actinobacteria isolated from Hundung limestone samples in Manipur, India using ARDRA as the molecular tool for preliminary classification. A total of 137 actinobacteria were clustered into 31 phylotypic groups based on the ARDRA pattern generated and representative of each group was subjected to 16S rRNA gene sequencing. Generic diversity of the limestone isolates consisted of Streptomyces (15 phylotypic groups), Micromonospora (4), Amycolatopsis (3), Arthrobacter (3), Kitasatospora (2), Janibacter (1), Nocardia (1), Pseudonocardia (1) and Rhodococcus (1). Considering the antimicrobial potential of these actinobacteria, 19 showed antimicrobial activities against at least one of the bacterial and candidal test pathogens, while 45 exhibit biocontrol activities against at least one of the rice fungal pathogens. Out of the 137 actinobacterial isolates, 118 were found to have at least one of the three biosynthetic gene clusters (PKS-I, PKS-II, NRPS). The results indicate that 86% of the strains isolated from Hundung limestone deposit sites possessed biosynthetic gene clusters of which 40% exhibited antimicrobial activities. It can, therefore, be concluded that limestone habitat is a promising source for search of novel secondary metabolites.